Luminous degradable fabric and method of making same
Patent Information
- Application Number
- CN202611061444.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-09-25
AI Technical Summary
为此,本申请提出一种夜光可降解织物及其制造方法,以解决夜跑安全警示与鞋面材料终端环保问题
本申请提供一种夜光可降解织物及其制造方法,织物包括夜光可降解线材,夜光可降解线材包括基材、夜光材料、光敏预降解助剂与生物降解促进剂;所述基材中的聚合物分子链在所述光敏预降解助剂与紫外光的共同作用下发生光氧化反应形成极性官能团及分子链断链;能够高亮长效发光且兼容光敏剂和微生物,同时具有物理耐受性、环保合规;在服役期可利用日光/紫外光储能并释放持久夜光,在废弃后,预先由光敏预降解助剂与光作用产生的聚合物分子链上的极性官能团及分子链断链能大幅加速生物降解促进剂引导的微生物降解过程,能够应用于对性能要求严苛的专业运动鞋服领域,有效解决运动装备行业日益突出的废弃物问题。
Abstract
Description
Technical Field
[0001] This application relates to the field of textile technology, and in particular to a biodegradable fabric that glows in the dark and a method for manufacturing the same. Background Technology
[0002] Night running has become one of the mainstream forms of exercise for urban dwellers. To ensure safety during night runs, existing running shoes use reflective materials such as reflective strips on the upper or active light-emitting devices such as LEDs. However, reflective materials rely on external light sources and fail in the absence of direct light, while LED devices have problems such as needing to be charged, circuit aging, increased weight, and more complex waste disposal. In addition, traditional luminous materials such as sulfides have short afterglow times, low brightness, and may contain heavy metals that are harmful to the environment.
[0003] Traditional running shoe uppers are mainly made of non-degradable synthetic fibers such as polyester (PET) and nylon. After being disposed of in landfills, these fibers can remain for hundreds of years, causing microplastic pollution. Due to environmental protection needs, bio-based biodegradable materials, such as polylactic acid (PLA), are currently being added to shoe uppers. While environmentally friendly, these materials have drawbacks such as poor heat resistance, low wet strength, and difficulty in achieving long-lasting luminescence, making it difficult to meet the requirements of high-performance running shoes.
[0004] Therefore, there is a lack of a comprehensive solution that can simultaneously address both safety warnings for night running and the environmental protection issues of shoe upper materials. Summary of the Invention
[0005] This application aims to address at least one of the technical problems existing in the prior art. To this end, this application proposes a biodegradable luminescent fabric and its manufacturing method to solve the problems of safety warnings for night running and the environmental protection of end-use shoe upper materials.
[0006] In a first aspect, this application provides a biodegradable fabric with bioluminescent properties, including biodegradable threads, wherein the biodegradable threads include a substrate, a bioluminescent material, a photosensitive pre-degradation agent, and a biodegradation promoter; The polymer molecular chains in the substrate undergo photo-oxidation under the combined action of the photosensitive pre-degradation agent and ultraviolet light to form polar functional groups and break the molecular chains.
[0007] In some embodiments: in the luminescent biodegradable wire: the substrate accounts for 85%-92% by mass, the luminescent material accounts for 5%-10% by mass, the photosensitive pre-degradation aid accounts for 1%-3% by mass, and the biodegradation promoter accounts for 2%-5% by mass.
[0008] In some embodiments, the luminescent material includes at least one of strontium aluminate rare earth luminescent material, silicate system luminescent material, and sulfur oxide luminescent material; The photosensitive pre-degradation aid includes at least one of photosensitive rare earth cerium complexes, organotransition metal salts, and benzophenone photoinitiators.
[0009] In some embodiments, the luminescent biodegradable thread comprises a core-sheath composite spun yarn, wherein the sheath of the core-sheath composite spun yarn comprises the substrate, and the luminescent material, photosensitive pre-degradation aid, and biodegradation promoter are disposed in the core layer of the core-sheath composite spun yarn.
[0010] In some embodiments, the total mass percentage of the luminescent material, photosensitive pre-degradation aid, and biodegradation promoter in the core layer of the core-sheath composite spinning is 11.5%-25.5%.
[0011] In some embodiments, the mass ratio of the sheath to the core layer in the sheath-core composite spinning is (20-40):(60-80). In the fabric, the total mass percentage of the luminescent material, photosensitive pre-degradable agent and biodegradable accelerator is 8%-18%.
[0012] In some embodiments, the fabric includes a three-dimensional mesh structure formed from the biodegradable luminescent yarn by a warp knitting process.
[0013] Secondly, this application also provides a method for manufacturing a biodegradable luminescent fabric, comprising: Prepare a phosphorescent biodegradable wire comprising a substrate, a phosphorescent material, a photosensitive pre-degradation agent, and a biodegradation promoter; Breathable fabrics with a three-dimensional mesh structure are prepared using the aforementioned biodegradable luminescent yarn through warp knitting. The breathable fabric is subjected to plasma surface activation treatment and then shaped to obtain a biodegradable fabric with luminescence. The biodegradable fabric is pre-activated with ultraviolet light.
[0014] In some embodiments, the plasma surface activation treatment includes: In a vacuum environment of 20Pa-50Pa, oxygen is introduced and plasma is excited to oxidize and modify the surface of the breathable fabric for 30s-90s.
[0015] In some embodiments, the wavelength of the ultraviolet light is 254nm-365nm, and the intensity of the ultraviolet light is 50W / cm². 2 -100W / cm 2 The pre-activation duration is 5-15 minutes.
[0016] The above-described one or more embodiments of this application have at least one or more of the following beneficial effects: This application provides a biodegradable luminescent fabric and its manufacturing method. The fabric includes biodegradable luminescent yarn, which comprises a substrate, a luminescent material, a photosensitive pre-degradation agent, and a biodegradation promoter. The polymer molecular chains in the substrate undergo photo-oxidation under the combined action of the photosensitive pre-degradation agent and ultraviolet light, forming polar functional groups and breaking the molecular chains. It can emit high-brightness, long-lasting light and is compatible with photosensitizers and microorganisms, while also exhibiting physical tolerance and environmental compliance. During its service life, it can utilize sunlight / ultraviolet light to store energy and release lasting luminescence. After disposal, the polar functional groups and broken molecular chains on the polymer molecular chains, pre-generated by the photosensitive pre-degradation agent and light, can significantly accelerate the microbial degradation process guided by the biodegradation promoter. This fabric can be applied to the field of professional sportswear with stringent performance requirements, effectively solving the increasingly prominent waste problem in the sports equipment industry.
[0017] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Detailed Implementation
[0018] The following describes some embodiments of this application. Those skilled in the art should understand that these embodiments are merely illustrative of the technical principles of this application and are not intended to limit the scope of protection of this application.
[0019] As described in the background section, current sports brands using traditional luminescent and reflective solutions employ PVC luminescent coatings or reflective strips to pursue safety warning functions. However, this fails to address the issue of the material's non-degradability, thus basing functionality on materials that exacerbate the environmental burden. This contradicts increasingly stringent global environmental regulations (such as EU carbon tariffs and plastic bans in various countries) and consumers' green consumption trends. Furthermore, the reflectivity relies on external light sources, increasing the burden on LEDs. Adding bio-based biodegradable materials, on the other hand, would be insufficient to meet the performance requirements of running shoes.
[0020] To address the aforementioned issues, this application creatively proposes a biodegradable luminescent fabric and its manufacturing method. The fabric includes biodegradable luminescent yarn, which comprises a substrate, a luminescent material, a photosensitive pre-degradation agent, and a biodegradation promoter. The polymer molecular chains in the substrate undergo photo-oxidation under the combined action of the photosensitive pre-degradation agent and ultraviolet light, forming polar functional groups and breaking the molecular chains. It exhibits high brightness and long-lasting luminescence while being compatible with photosensitizers and microorganisms, possessing physical tolerance and environmental compliance. During its service life, it can utilize sunlight / ultraviolet light to store energy and release lasting luminescence. After disposal, the "active sites" (highly chemically reactive molecular structural sites) on the polymer molecular chains pre-generated by the photosensitive pre-degradation agent and light significantly accelerate the microbial degradation process guided by the biodegradation promoter. This fabric can be applied to the field of professional sportswear with stringent performance requirements, effectively solving the increasingly prominent waste problem in the sports equipment industry.
[0021] The present application will be described in detail below through specific embodiments.
[0022] Specifically, this application provides a biodegradable fabric with luminescent properties, including biodegradable yarn. The biodegradable yarn includes a substrate, a luminescent material, a photosensitive pre-degradation agent, and a biodegradation promoter. The polymer molecular chains in the substrate undergo photo-oxidation under the combined action of the photosensitive pre-degradation agent and ultraviolet light to form polar functional groups and break the molecular chains.
[0023] Specifically, under the combined action of photosensitive pre-degradation aids and ultraviolet light, the polymer molecular chains in the substrate undergo photo-oxidation reactions to form polar functional groups such as carbonyl (C=O) and carboxyl (-COOH) groups, resulting in molecular chain breaks. These are the preferred targets for subsequent microbial and enzyme attacks. Molecular chain breaks occur when the long polymer molecules in the substrate break covalent bonds at the carbon-carbon (CC) or carbon-heteroatom (such as CO) bonds in their main chain, causing a long-chain molecule to cleave into two or more shorter-chain molecules with lower molecular weights.
[0024] By testing parameters such as carbonyl index, surface water contact angle, and number-average molecular weight before and after ultraviolet light irradiation, it can be determined whether polar functional groups are formed and whether the molecular chains are broken after ultraviolet light irradiation.
[0025] For example, by measuring and calculating the absorbance of the carbonyl peak using a Fourier transform infrared spectrometer, it was found that after ultraviolet irradiation, the carbonyl index in the substrate was 1.5-3 times that before irradiation, the surface water contact angle decreased by more than 20° compared to before irradiation, and the number-average molecular weight decreased by 10%-35% compared to before irradiation. The synergistic changes of the above parameters jointly proved the successful construction of polar functional groups and molecular chain scission in the substrate.
[0026] From the perspective of microscopic reaction mechanisms, the scientific principle of molecular chain scission and subsequent degradation can be divided into two key stages: The first stage is the "photo-oxidative pre-damage reaction." During the manufacturing stage, ultraviolet light pre-activation and during service life, sunlight (especially ultraviolet light) irradiation excites the photosensitive pre-degradation aids encapsulated inside the substrate, generating highly active free radicals. These free radicals induce local breakage of the originally chemically inert and structurally stable covalent bonds (such as C-C bonds or CO bonds) on the main chain of the substrate (PET / TPU blend polymer), breaking them into short-chain molecules with low molecular weight. Simultaneously, sufficient amounts of low-concentration carbonyl (C=O) and carboxyl (-COOH) polar functional groups, i.e., "active sites," are generated at the ends of these breakages. The modification will not affect the overall mechanical support and service life of the finished fabric. The second stage is the "biological and enzymatic degradation stage". When the fabric is discarded and enters an anaerobic environment such as landfill, the biodegradation promoter begins to adjust the hydrophilic properties on the plastic surface and guides up to hundreds of natural native microorganisms to attach to the surface and form a biofilm. The microorganisms then secrete specific oxidases (such as laccase, peroxidase, etc.). These enzymes can accurately identify the oxygen-containing polar functional group targets formed by the chain breakage in the early stage and launch an efficient attack on them. They quickly cut the long polymer chain along these breakage gaps, thereby gradually degrading the macromolecules into harmless small molecules such as carbon dioxide (CO2), water (H2O) or methane (CH4).
[0027] The substrate is the main skeleton of the wire and includes biodegradable polymers. By way of example and not limitation, the substrate may include at least one of polylactic acid (PLA), polybutylene adipate terephthalate (PBAT), polyethylene terephthalate (PET), and thermoplastic polyurethane elastomer (TPU), which gives the wire basic mechanical properties and formability.
[0028] As a preferred option, the substrate comprises polyethylene terephthalate (PET) and thermoplastic polyurethane elastomer (TPU). PET has high strength, excellent tear resistance, and wear resistance, while TPU has high elasticity, bend resistance, wear resistance, and scratch resistance. It also has good compatibility with luminescent materials, photosensitive pre-degradable additives, and biodegradation accelerators. The composite of PET and TPU provides strong support and high elasticity, meeting the stringent requirements of athletic running shoe uppers. It also adapts to the requirements for adding luminescent materials, photosensitive pre-degradable additives, and biodegradation accelerators, as well as the spinning requirements and manufacturing process requirements of the yarn.
[0029] The substrate is the structural support core of the wire. It uses PET / TPU blended polymer as the main raw material. Its originally chemically inert and structurally stable polymer molecular chains can undergo a controllable photo-oxidation modification reaction under the dual action of the photosensitive pre-degradation aid and the energy excitation of ultraviolet light. This forms highly chemically reactive molecular structural sites in the molecular chains. These active sites are mainly carbonyl groups (C=O) and can also derive oxygen-containing polar functional groups such as hydroxyl and carboxyl groups. This is not a complete breakage of the polymer backbone, but only a local modification of the chemical structure of the molecular chains. It will not destroy the mechanical support performance of the composite matrix, and can become the core target for microbial recognition and attack during the subsequent biodegradation process. During the fabric's service life, generating sufficient and low-concentration active sites on the polymer molecular chain will not affect the fabric's mechanical properties or service life, but will also improve degradation efficiency for subsequent degradation. When the fabric is discarded and enters anaerobic environments such as landfills, these active sites will become the key breakthrough for microbial degradation. Oxidases such as laccase and peroxidase secreted by microorganisms can act efficiently on the active sites, quickly severing the polymer backbone. Combined with the microbial guidance of biodegradation promoters, the originally difficult-to-degrade PET / TPU polymers can be rapidly biodegraded, completely solving the microplastic pollution problem of traditional synthetic fiber fabrics.
[0030] In this application, the term "biodegradation accelerator" refers to a functional additive added to materials such as plastics, fibers, and coatings. Its core function is to accelerate and enhance the biodegradation process of materials in natural environments (soil, seawater, compost), ultimately decomposing macromolecules into harmless substances such as CO2, water, or methane. In some embodiments: in the luminescent biodegradable wire: the substrate accounts for 85%-92% by mass, the luminescent material accounts for 5%-10% by mass, the photosensitive pre-degradation additive accounts for 1%-3% by mass, and the biodegradation accelerator accounts for 2%-5% by mass.
[0031] Optionally, in the luminescent biodegradable wire, the mass percentage of the substrate can be 85%, 87%, 90%, 91%, 92%, or any value within the above mass percentage range. For space limitations and for the sake of brevity, this application will not exhaustively list all specific values within the range. The mass percentage of the luminescent material can be 5%, 6.2%, 7%, 8.5%, 9%, 9.6%, 10%, or any value within the above mass percentage range. For space limitations and for the sake of brevity, this application will not exhaustively list all specific values within the range. The mass percentage of the photosensitive pre-degradable additive... The mass percentage can be 1%, 1.2%, 1.5%, 1.7%, 2%, 2.3%, 2.5%, 2.8%, 3%, or any value within the above mass percentage range. Due to space limitations and for the sake of brevity, this application will not exhaustively list the specific values included in the range. The mass percentage of the biodegradation promoter can be 2%, 2.2%, 2.5%, 3.1%, 3.7%, 4%, 4.5%, 5%, or any value within the above mass percentage range. Due to space limitations and for the sake of brevity, this application will not exhaustively list the specific values included in the range.
[0032] The above-mentioned formulation system is not an independent action of a single component, but rather the proportions of each component are mutually adapted and mutually constrained, so that the three functions of luminescence, mechanics, and degradation form an organic whole without antagonism. For the first time, it has achieved a synergistic formulation that can simultaneously meet the mechanical requirements of high-performance running shoe uppers, the luminescence requirements for night running safety, and the environmentally friendly degradation requirements at the end. Through the upper and lower limits of each component, the material has the following core performance throughout its entire life cycle: high toughness and high brightness during the service period, and controllable and efficient degradation effect during the disposal period. At the same time, it is compatible with processes such as core spinning and warp knitting, and has practical value for industrial production.
[0033] In some embodiments, the luminescent material includes at least one of strontium aluminate rare earth luminescent material, silicate system luminescent material, and sulfur oxide luminescent material; it can absorb visible light and ultraviolet light, store energy in lattice defects, and continuously release visible light (afterglow) in dark environments to provide passive safety warnings.
[0034] Preferably, the luminescent material includes strontium-acid rare earth luminescent material. Strontium-acid rare earth luminescent material can simultaneously meet four stringent conditions: high brightness and long-lasting luminescence (solving safety issues during night running), chemical inertness (compatible with photosensitizers and microorganisms), physical resistance (suitable for warp knitting processes), and environmental compliance.
[0035] The photosensitive pre-degradation aid includes at least one of photosensitive rare-earth cerium complexes, organotransition metal salts, and benzophenone-based photoinitiators. Under ultraviolet light irradiation, the photosensitive pre-degradation aid generates free radicals and induces oxidation of the substrate's molecular chains. During the shoe's service life, exposure to sunlight (especially ultraviolet light) leads to a photo-oxidation reaction, introducing oxygen-containing active groups such as carbonyl groups (C=O) onto the polymer molecular chains of the substrate. These pre-damaged molecular chains become more vulnerable targets for microorganisms when subsequently introduced into anaerobic environments (such as landfills), thereby improving decomposition efficiency.
[0036] In some embodiments, the biodegradation promoter includes a microbial-free universal degradation promoter that uses small biological molecules to attract native microbial communities. It is safe, easy to process, and suitable for various recalcitrant plastics such as PE, PP, and PET.
[0037] Preferably, the biodegradation promoter includes ECO elements. It should be noted that "ECO elements" are a novel type of plastic biodegradable additive. By adding trace amounts to the plastic substrate, it enables the plastic substrate to achieve effective biodegradation in the natural environment. ECO elements alter the properties of the plastic surface, such as reducing drainage, creating favorable conditions for microbial attachment and reproduction, i.e., biofilm. Biofilms attract up to 600 different types of microorganisms from soil or water. When microorganisms degrade plastics, they secrete enzymes to break down long polymer chains. The role of ECO elements is to accelerate this process, helping microorganisms gradually convert large plastic molecules into harmless substances such as water, carbon dioxide, or methane.
[0038] In some embodiments, the luminescent biodegradable thread comprises a core-sheath composite spun yarn, wherein the sheath of the core-sheath composite spun yarn comprises the substrate, and the luminescent material, photosensitive pre-degradation aid, and biodegradation promoter are disposed in the core layer of the core-sheath composite spun yarn.
[0039] The substrate forms a skin layer encapsulating a core layer containing luminescent materials, photosensitive pre-degradable agents, and biodegradation promoters. This provides physical isolation of the luminescent materials, photosensitive pre-degradable agents, and biodegradation promoters during melt spinning, preventing these components from causing spinneret wear or blockage during melting, or from causing the photosensitive pre-degradable agents and biodegradation promoters to decompose and migrate out. Furthermore, since the photosensitive pre-degradable agents require UV excitation to generate active sites on the substrate, an appropriately thick skin layer allows some UV light to penetrate to the core layer, triggering the agent reaction. Simultaneously, it slows down the rapid intrusion of degradation media such as moisture and oxygen, allowing the degradation process to gradually advance from skin defects or the surface towards the core layer, achieving a stable service life and a controllable degradation gradient after disposal.
[0040] In some embodiments, in the core layer of the core-sheath composite spinning, the total mass percentage of the luminescent material, photosensitive pre-degradation aid, and biodegradation accelerator is 11.5%-25.5%. Optionally, the total mass percentage of the luminescent material, photosensitive pre-degradation aid, and biodegradation accelerator can be 11.5%, 13.7%, 15%, 18.5%, 20.4%, 22.9%, 25.5%, or any value within the above mass percentage range. Due to space limitations and for the sake of brevity, this application will not exhaustively list the specific values included in the range. The core layer includes a substrate, luminescent material, photosensitive pre-degradable agent, and biodegradation accelerator. In the core layer of the skin-core composite spinning, if the total mass percentage of the luminescent material, photosensitive pre-degradable agent, and biodegradation accelerator is less than 11.5%, the concentration of functional additives is insufficient, which can easily lead to failure of luminescent function, photosensitive pre-degradable agent, and biodegradable function. In the core layer of the skin-core composite spinning, if the total mass percentage of the luminescent material, photosensitive pre-degradable agent, and biodegradation accelerator is greater than 25.5%, the concentration of functional additives is too high, which can easily destroy the continuous phase structure of the substrate in the core layer. The rigid luminescent material cannot be effectively wrapped by the substrate, resulting in a sharp increase in the brittleness of the core layer and a significant decrease in bending resistance, which cannot meet the performance requirements of the shoe upper.
[0041] In some embodiments, the mass ratio of the sheath to the core layer in the sheath-core composite spinning is (20-40):(60-80). Optionally, the mass ratio of the sheath to the core layer in the sheath-core composite spinning can be 20:60, 20:67, 37:60, 40:60, 20:80, 35:72, 41:68, 40:73, 40:80, or any value within the above mass ratio range. Due to space limitations and for the sake of brevity, this application will not exhaustively list the specific ratios included in the range.
[0042] In the fabric, the total mass percentage of the luminescent material, photosensitive pre-degradation agent, and biodegradation accelerator is 8%-18%. Optionally, the total mass percentage of the luminescent material, photosensitive pre-degradation agent, and biodegradation accelerator in the fabric can be 8%, 10.5%, 12.6%, 15%, 16.5%, 17.3%, 18%, or any value within the above mass percentage range. Due to space limitations and for the sake of brevity, this application will not exhaustively list the specific values included in the range.
[0043] In some embodiments, the fabric includes a three-dimensional mesh structure formed from the biodegradable luminescent yarn by a warp knitting process.
[0044] Specifically, the three-dimensional mesh structure comprises two layers of mesh fabric and a central "Z"-shaped connecting thread. This inherent thickness allows the luminescent or degradation reactions of the luminescent material, photosensitive pre-degradation aid, and biodegradation promoter to occur within a three-dimensional space, resulting in more significant effects. Furthermore, the open and permeable structure provides excellent channels for degradation triggering conditions such as light, air, and moisture, facilitating efficient oxidative degradation. The three-dimensional structure itself provides excellent resilience and compressive strength, compensating for the potential strength reduction in the core layer of a core-skin structure due to the filling of additives.
[0045] This application also provides a method for manufacturing a biodegradable luminescent fabric, comprising: S1. Prepare a phosphorescent biodegradable wire comprising a substrate, a phosphorescent material, a photosensitive pre-degradation agent, and a biodegradation promoter.
[0046] S2. A breathable fabric with a three-dimensional mesh structure is prepared using the aforementioned biodegradable luminescent yarn through warp knitting.
[0047] S3. The breathable fabric is subjected to plasma surface activation treatment and then shaped to obtain a biodegradable fabric that glows in the dark.
[0048] S4. Pre-activate the biodegradable fabric with ultraviolet light.
[0049] In some embodiments, step S1 includes: A biodegradable luminescent thread is prepared by using a core-sheath composite melt spinning process, with the substrate as the sheath and the substrate, luminescent material, photosensitive pre-degradation agent and biodegradation promoter as the core.
[0050] The substrate includes TPU and PET, wherein the mass ratio of TPU to PET is adjusted according to the process.
[0051] In some embodiments, the process of using a core-sheath composite melt spinning process to prepare a biodegradable bioluminescent thread, using the substrate as the sheath and the substrate, a luminescent material, a photosensitive pre-degradation agent, and a biodegradation promoter as the core, includes: A masterbatch for the core layer was prepared and a skin substrate melt was prepared using the masterbatch method. The core layer masterbatch includes a substrate, a luminescent material, a photosensitive pre-degradation aid, and a biodegradation promoter. The core-sheath composite spun yarn is formed by fusion spinning of core-sheath composite yarn through a composite spinneret using a core-sheath composite melt spinning machine.
[0052] Because the luminescent material, photosensitive pre-degradation aid, and biodegradation accelerator are prone to agglomeration when directly melt-blended with the substrate, a high-concentration core layer functional masterbatch is first prepared using the masterbatch method, and then diluted and blended with the core layer substrate particles. This ensures that the luminescent material, photosensitive pre-degradation aid, and biodegradation accelerator are uniformly dispersed at the nanoscale in the core layer. In some examples, the specific steps are as follows: The core PET particles, TPU particles, luminescent material, photosensitive pre-degradation agent, and biodegradation promoter are placed in a vacuum drying oven and dried at 80℃-100℃ for 4-6 hours to remove moisture from the raw materials, thus avoiding the generation of bubbles during melt spinning, which would damage the core-sheath structure and the mechanical properties of the wire.
[0053] According to the preset ratio, the dried core substrate particles (PET+TPU), luminescent material, photosensitive pre-degradation agent, biodegradation promoter and dispersant are added to a high-speed mixer and mixed at 1000r / min-1500r / min for 15min-20min to achieve preliminary uniform mixing of materials and obtain initial mixed materials.
[0054] The initial mixed material is added to a twin-screw extruder for melt blending, extrusion, and granulation. The extrusion process parameters are: zone 1 temperature 160℃-170℃, zone 2 temperature 170℃-180℃, zone 3 temperature 180℃-190℃, die head temperature 180℃-185℃, and screw speed 200r / min-300r / min.
[0055] After the extruded melt is cooled and shaped in a water-cooling tank (25℃-30℃), it is cut into core layer functional masterbatches of 3mm-5mm by a pelletizer and then dried for later use.
[0056] Dried TPU and PET particles are added to a single-screw extruder (for skin layers) for melt plasticization to prepare a homogeneous skin melt. Process parameters: melt temperature 170℃-185℃, screw speed 150r / min-200r / min. After mixing in a static mixer, the melt is conveyed to the skin flow channel of the skin-core composite spinneret for later use (melt viscosity controlled at 1000-2000Pa). s, which matches the melt viscosity of the core layer to avoid core layer deviation during spinning.
[0057] A core-sheath composite melt spinning machine is used, in which the core layer melt and sheath melt are delivered separately through dual melt channels, and then fused and spun through a composite spinneret to form a core-sheath structure nascent filament consisting of a pure sheath substrate, a core substrate with luminescent material, a photosensitive pre-degradation agent, and a biodegradation promoter. The specific steps are as follows: The core layer functional masterbatch is diluted and mixed with dried core layer substrate particles (PET+TPU) according to a specified ratio. This mixture is then added to a separate single-screw extruder dedicated to the core layer for melt plasticization. The process parameters are matched to those of the skin layer extruder: Zone 1 165℃-175℃, Zone 2 175℃-185℃, Zone 3 185℃-195℃, and die head 185℃-190℃. The melt is then conveyed to the core layer central flow channel of the composite spinneret after passing through a static mixer. The core layer melt flows out from the center of the spinneret, while the skin layer melt flows out from the annular flow channel outside the core layer melt. The two melts simultaneously at the spinneret exit and are extruded through 0.2mm-0.4mm spinneret orifices to form a core-skin structure nascent filament. After the nascent filaments are extruded, they are cooled and shaped by side blowing air at 25℃-30℃ with a side blowing air speed of 0.5m / s-1.0m / s. Then, they are pre-stretched by stretching rollers with a stretching ratio of 2.5-3.5 to improve the tensile strength and structural density of the nascent filaments.
[0058] The cross-sectional area ratio of the sheath-core flow channel in the composite spinneret is matched with the mass ratio of the sheath to the core layer. During the spinning process, the melt pressure is kept stable at 5MPa-8MPa to avoid pressure fluctuations that could lead to uneven sheath-core structure.
[0059] After being drawn, the nascent yarn undergoes heat setting, oiling, and winding processes to produce a finished biodegradable luminescent yarn. This process ensures the yarn's elasticity, bending resistance, and abrasion resistance, while also improving the yarn's compatibility with the loom.
[0060] Heat setting: The pre-stretched filament bundle is fed into a heat setting machine and set with hot air at a temperature of 80℃-100℃ for 5s-10s. It is then lightly stretched twice with a stretching ratio of 1.1-1.3 to eliminate internal stress in the filament bundle, improve the dimensional stability of the wire, and prevent shrinkage and deformation during subsequent weaving. Oiling: After setting, the yarn bundles are oiled in an oiling tank. The oil used is a textile-specific antistatic smoothing oil with an oiling rate of 0.8%-1.2% to reduce the surface friction coefficient of the yarn, prevent needle grinding and yarn breakage during warp knitting, and improve the antistatic properties of the yarn to prevent dust accumulation during use.
[0061] Winding process: The oiled yarn bundles are wound into finished yarn in tubes by a winding machine with a linear density of 150D-300D to meet the warp feeding requirements of the warp knitting process.
[0062] The finished wire after winding undergoes multiple tests, including structural testing, mechanical property testing, luminescence performance testing, and process compatibility testing. Only after passing these tests can it be used for warp knitting in step S2.
[0063] In some embodiments, step S2 includes: Using a double needle bed warp knitting machine, the warp feed rate of the comb bar is controlled at 1200mm / rack-1800mm / rack to form a breathable fabric with a three-dimensional mesh structure.
[0064] In some embodiments, the plasma surface activation treatment includes: In a vacuum environment of 20Pa-50Pa, oxygen is introduced and plasma is excited to oxidize and modify the surface of the breathable fabric for 30s-90s. Optionally, the vacuum degree of the vacuum environment can be 20Pa, 25Pa, 31Pa, 35Pa, 40Pa, 46Pa, 50Pa, or any point value within the above vacuum degree range. Due to space limitations and for the sake of brevity, this application will not exhaustively list the specific point values included in the range.
[0065] The plasma oxidation modification time on the surface of the breathable fabric can be 30s, 47s, 50s, 62s, 70s, 86s, 90s, or any value within the above range. Due to space limitations and for the sake of brevity, this application will not exhaustively list the specific values included in the range.
[0066] In some embodiments, the wavelength of the ultraviolet light is 254nm-365nm, and the intensity of the ultraviolet light is 50W / cm². 2 -100W / cm 2 The pre-activation duration is 5-15 minutes. Optionally, the wavelength of the ultraviolet light can be 254nm, 270nm, 282nm, 295nm, 306nm, 324nm, 337nm, 348nm, 365nm, or any value within the above wavelength range. For space limitations and for the sake of brevity, this application will not exhaustively list all the specific values included in the range. The intensity of the ultraviolet light can be 50W / cm². 2 65W / cm 2 76W / cm 2 82W / cm 2 93W / cm 2 100W / cm 2 The light intensity value may be any value within the range of the above light intensity values. Due to space limitations and for the sake of brevity, this application will not exhaustively list all the specific values included in the range. The pre-activation duration may be 5 min, 6 min, 8 min 20 s, 9 min 30 s, 10 min, 13 min 15 s, 15 min, or any value within the above duration range. Due to space limitations and for the sake of brevity, this application will not exhaustively list all the specific values included in the range.
[0067] In some embodiments, the method further includes: after plasma oxidizes and modifies the surface of the breathable fabric, the breathable fabric is then subjected to a setting treatment at 180°C.
[0068] The solution provided in this application will be further described below with reference to specific embodiments.
[0069] Example 1: This example provides a biodegradable luminescent fabric, manufactured as follows: A biodegradable luminescent yarn is prepared by mixing a substrate, a luminescent material, a photosensitive pre-degradation agent, and a biodegradation accelerator. The substrate is a 7:3 mass ratio of PET to TPU, comprising 89% of the yarn's mass. The luminescent material is strontium aluminate rare earth luminescent material, comprising 7% of the mass. The photosensitive pre-degradation agent is a photosensitive rare earth cerium complex, comprising 2% of the mass. The biodegradation accelerator comprises 2% of the mass. The yarn is then spun into a core-sheath composite: the sheath to core mass ratio is 30:70; the core contains 14% of the total mass of the luminescent material, photosensitive pre-degradation agent, and biodegradation accelerator. The biodegradable luminescent fabric is then woven from the core-sheath composite yarn, with the total mass of the luminescent material, photosensitive pre-degradation agent, and biodegradation accelerator comprising 8.4% of the fabric's mass. The fabric is woven into a three-dimensional mesh structure using a double-needle bed warp knitting machine, with a guide bar feed rate of 1500 mm / rack. The woven three-dimensional mesh structure was subjected to plasma treatment: vacuum degree 35 Pa, oxygen-excited plasma oxidation modification for 60 s, and setting at 180℃. It was then pre-activated with ultraviolet light: wavelength 310 nm, light intensity 80 W / cm², duration 10 min.
[0070] Upon testing, the biodegradable fabric obtained in Example 1, after UV pre-activation treatment, exhibited the following core macroscopic characterization parameters determined by Fourier Transform Infrared Spectroscopy (FTIR) and Gel Permeation Chromatography (GPC): the carbonyl index in the substrate increased to 2.1 times that before irradiation; the water contact angle on the substrate surface decreased significantly by 24° compared to before irradiation; and the number-average molecular weight (Mn) of the substrate decreased by 18% compared to before irradiation. These synergistic changes in parameters fully demonstrate the successful construction of polar functional groups and molecular chain scission in the substrate.
[0071] Example 2: This example provides a biodegradable luminescent fabric, differing from Example 1 in that: the mass ratio of PET to TPU in the substrate is 65:35, the substrate accounts for 87% of the total mass of the yarn, the luminescent material is a silicate-based luminescent material, accounting for 8% of the total mass of the yarn, the photosensitive pre-degradation agent is a benzophenone-based photoinitiator, and the biodegradation accelerator accounts for 2%. In the core-sheath composite spinning, the mass ratio of the sheath to the core layer is 20:80, and the total mass percentage of the luminescent material, photosensitive pre-degradation agent, and biodegradation accelerator in the core layer is 20%. The total mass percentage of the luminescent material, photosensitive pre-degradation agent, and biodegradation accelerator in the fabric is 12%. During warp knitting, the guide bar feed rate is 1600 mm / rack. The plasma treatment involves a vacuum degree of 25 Pa, oxygen-excited plasma oxidation modification for 80 s, ultraviolet pre-activation wavelength of 254 nm, light intensity of 90 W / cm², and a duration of 12 min.
[0072] Testing revealed that the biodegradable luminescent fabric obtained in Example 2, after UV pre-activation treatment, exhibited the following core macroscopic characterization parameters: the carbonyl index in the substrate increased to 2.6 times that before irradiation; the water contact angle on the substrate surface decreased by 28° compared to before irradiation; and the number-average molecular weight (Mn) of the substrate decreased by 25% compared to before irradiation. These data collectively demonstrate that this scheme achieves efficient and excellent polar functional group construction and local chain scission modification under different formulations and process parameter windows.
[0073] Comparative Example 1: The only difference between this comparative example and Example 1 is that the mass ratio of the cortex to the core is adjusted to 15:85 (the core content exceeds the upper limit of 80), and the other parameters are the same as those in Example 1.
[0074] Comparative Example 2: The only difference between this comparative example and Example 1 is that the mass ratio of the cortex to the core is adjusted to 45:55, and the other parameters are the same as those in Example 1.
[0075] Comparative Example 3: The only difference between this comparative example and Example 1 is that the mass ratio of the luminescent material (strontium aluminate rare earth luminescent material) is adjusted to 3% (below the lower limit of 5%), and the mass ratio of the substrate is adjusted to 93% accordingly. The other parameters are the same as those in Example 1.
[0076] Comparative Example 4: The only difference between this comparative example and Example 1 is that the mass percentage of the luminescent material (strontium aluminate rare earth luminescent material) is adjusted to 13% (above the upper limit of 10%), and the mass percentage of the substrate is correspondingly adjusted to 83% (below the lower limit of 85%). All other parameters are the same as in Example 1. Test results show that although the luminescence performance is improved (initial afterglow brightness increased by approximately 15%), due to the low substrate percentage, the tensile strength of the filament decreases to 72% of that in Example 1, and the elongation at break decreases to 65% of that in Example 1, failing to meet the basic mechanical performance requirements of running shoe uppers (tensile strength must be ≥2.5 cN / dtex). Furthermore, the high concentration of luminescent inorganic powder causes severe wear of the spinneret orifices during melt spinning, shortening the spinneret replacement cycle from 2 months to 2 weeks, resulting in poor process feasibility. Simultaneously, the substrate percentage being below 85% significantly deteriorates the spinnability of the filament, leading to uneven core-sheath structure and a defect rate exceeding 35%.
[0077] Comparative Example 5: The only difference between this comparative example and Example 1 is that the mass ratio of the photosensitive pre-degradation aid is adjusted to 0.5% (below the lower limit of 1%), and the mass ratio of the biodegradation promoter is adjusted to 3.5% accordingly. After UV pre-activation, the density of active sites (carbonyl C=O) formed on the PET molecular chain is only 8% of that in Example 1. Comparative Example 6: The only difference between this comparative example and Example 1 is that the mass ratio of the photosensitive pre-degradation agent is adjusted to 5%, no biodegradation promoter is added, and the substrate is adjusted to 87%.
[0078] Comparative example biodegradation accelerator 7: The only difference between this comparative example and Example 1 is that the mass ratio of the biodegradation accelerator is adjusted to 1%, and the mass ratio of the substrate is adjusted to 90% accordingly.
[0079] Comparative Example 8: The only difference between this comparative example and Example 1 is that the mass ratio of the biodegradation promoter is adjusted to 7%, and the mass ratio of the substrate is adjusted to 84%.
[0080] Comparative Example 9: The only difference between this comparative example and Example 1 is that the plasma processing vacuum degree is adjusted to 15 Pa (below the lower limit of 20 Pa) and the processing time is 60 s.
[0081] Comparative Example 10: The only difference between this comparative example and Example 1 is that the plasma treatment time was adjusted to 15s and the vacuum degree was 35Pa.
[0082] Comparative Example 11: The only difference between this comparative example and Example 1 is that the plasma treatment time is adjusted to 120s (higher than the upper limit of 90s).
[0083] Comparative Example 12: The only difference between this comparative example and Example 1 is that the UV pre-activation light intensity is adjusted to 30W / cm² (below the lower limit of 50W / cm²), while the other UV parameters remain unchanged.
[0084] Comparative Example 13: The only difference between this comparative example and Example 1 is that the intensity of the ultraviolet pre-activation light is adjusted to 120W / cm² (higher than the upper limit of 100W / cm²).
[0085] Comparative Example 14: The only difference between this comparative example and Example 1 is that the UV pre-activation time was adjusted to 2 min (below the lower limit of 5 min). The time was too short to fully activate the photosensitive pre-degradation aid, and the active site density was only 35% of that in Example 1.
[0086] Comparative Example 15: The only difference between this comparative example and Example 1 is that the UV pre-activation time was adjusted to 20 min (higher than the upper limit of 15 min). Excessive time resulted in over-photo-oxidation of the polymer molecular chains, causing the tensile strength to decrease to 63% of that in Example 1, and the processing energy consumption was too high, making industrial production costs unacceptable.
[0087] The fabric samples prepared from Examples 1-2 and Comparative Examples 1-15 were subjected to comprehensive performance comparison tests. The test items and standards are as follows: (1) Tensile strength and elongation at break: Refer to GB / T 3923.1 to test the warp tensile strength (cN / dtex). (2) Luminous performance: Refer to DIN 67510 to test the initial brightness of afterglow (mcd / m²) and the duration of afterglow (h). (3) Degradation performance: Refer to ASTM D5511 to test the anaerobic landfill degradation rate (%) after 1288 days. (4) Surface quality: Visual inspection and SEM scanning electron microscopy were used to observe the surface morphology of the fibers and evaluate the wear of the spinneret holes and the degree of eccentricity. (5) Aging resistance: Refer to GB / T 3923.1 to test the tensile strength retention rate (%) after 6 months of UV pre-activation.
[0088] Test results show that: Example 1 (shell-to-core ratio 30:70) has a tensile strength of 2.8 cN / dtex, an initial afterglow brightness ≥500 mcd / m², an afterglow duration ≥8h, a predicted degradation rate ≥60% (1288 days), and a 6-month strength retention rate ≥90%. Example 2 (shell-to-core ratio 20:80) has a tensile strength of 2.5 cN / dtex, an initial afterglow brightness ≥450 mcd / m², an afterglow duration ≥8h, a predicted degradation rate ≥65% (1288 days), and a 6-month strength retention rate ≥85%.
[0089] Comparative Example 1 suffered from a high spinning failure rate and severe core misalignment due to an excessively thin sheath layer, resulting in the inability to obtain qualified fabrics. During melt spinning, an excessively high core layer ratio led to an unstable sheath-core structure. An excessively thin sheath layer failed to effectively encapsulate the core layer functional additives, exacerbating spinneret wear and causing significant core leakage and core misalignment. The resulting yarn had a rough surface and significantly reduced mechanical strength, failing to meet the requirements of subsequent warp knitting processes. Simultaneously, the excessively thin sheath layer allowed for excessive UV light penetration, causing the photosensitive pre-degradation additives to become over-activated within the normal service life. The density of active sites on the PET molecular chain was too high, and tests showed that the fabric's tensile strength dropped to below 60% of its initial value after only three months of use.
[0090] In Comparative Example 2, the sheath was too thick and the core layer too thin. While the tensile strength met the standard, the excessively thick sheath, although ensuring mechanical properties and wire surface quality, resulted in an overly strong shielding effect against ultraviolet light. Less than 30% of the ultraviolet light reached the core layer, leading to insufficient activation of the photosensitive pre-degradation agent. The density of active sites formed on the PET molecular chain was less than 15% of that in Example 1. The degradation rate after 1288 days was only 28%, and the luminescence brightness decreased by 40%.
[0091] In Comparative Example 3, the proportion of luminescent material was too low. Test results showed that the initial brightness of the afterglow was only 140 mcd / m², which did not meet the safety warning requirements. The afterglow duration (the time required for the brightness to decay to 20% of the initial value) was less than 1 hour, far from meeting the safety warning requirements for the entire night (≥8 hours). In addition, the low concentration of luminescent material caused the proportion of total functional additives in the core layer to drop to 10%, which is lower than the lower limit of 11.5%, and the intensity of the microbial-induced degradation signal of the biodegradation promoter was correspondingly weakened.
[0092] In Comparative Example 4, the proportion of luminescent material was too high. Test results showed that although the luminescent performance of the fabric was improved (initial brightness of afterglow increased by about 15%), the tensile strength was only 2.0 cN / dtex due to the low proportion of substrate material. The tensile strength of the yarn decreased to 72% of that in Example 1, resulting in poor process feasibility. The elongation at break decreased to 65% of that in Example 1, failing to meet the basic mechanical performance requirements of running shoe uppers (tensile strength must be ≥2.5 cN / dtex). In addition, the high concentration of luminescent inorganic powder caused severe wear of the spinneret orifices during melt spinning, shortening the spinneret replacement cycle from 2 months to 2 weeks, further complicating process feasibility. Simultaneously, the substrate material proportion being less than 85% significantly deteriorated the spinnability of the yarn, resulting in uneven core-sheath structure and a defect rate exceeding 35%.
[0093] In Comparative Example 5, the proportion of photosensitive pre-degradation aid was too low. In the anaerobic landfill degradation test (ASTM D5511), the degradation rate was only 18% after 1288 days, which was significantly lower than the predicted value of over 60% in Example 1. This proves that the photosensitive pre-degradation aid cannot effectively establish the active site network required for degradation when it is below the lower limit.
[0094] In Comparative Example 6, the proportion of photosensitive pre-degradable additives was too high. Test results showed that the density of active sites on the PET molecular chains was too high after UV pre-activation, resulting in significant localized over-oxidation of the molecular chains within the service life. This caused the tensile strength of the fabric to drop to less than 50% of its initial value within 6 months, failing to meet the normal service life requirements (≥1 year) for running shoes. Simultaneously, excessive photosensitizer migrated to the leather surface, causing the fabric surface to yellow and discolor, resulting in substandard appearance quality.
[0095] In Comparative Example 7, the mass ratio of ECO element was too low. In the anaerobic landfill degradation test (ASTM D5511), the degradation rate was only 22% after 1288 days, which was far lower than the more than 60% (predicted value) in Example 1. This proves that when the concentration of biodegradation promoter is insufficient, an effective microbial chemotactic signal gradient cannot be formed, and the degradation efficiency is significantly reduced.
[0096] In Comparative Example 8, the proportion of biodegradable accelerator was higher while the proportion of substrate was lower. Test results showed that the tensile strength of the yarn decreased to 68% of that in Example 1, failing to meet the mechanical requirements of running shoe uppers. Furthermore, the high concentration of biodegradable accelerator partially decomposed during melt spinning, producing an irritating odor. This necessitates additional ventilation and exhaust gas treatment equipment in the spinning workshop, making industrial production infeasible. Simultaneously, excessive biodegradable accelerators begin to slowly release chemotactic signaling substances even during normal use, causing the fabric to develop an odor in humid environments, resulting in a poor user experience.
[0097] The test results of Comparative Examples 9-11 show that: Tensile strength decreased by 22%-35% or surface energy was insufficient; too low vacuum led to excessive oxygen plasma density, excessive etching of the fabric surface, microcracks on the fiber surface, and tensile strength decreased to 78% of that in Example 1; too short a processing time resulted in insufficient surface oxidation modification, with surface energy only increasing to 35mN / m (≥42mN / m in Example 1), insufficient adhesion of the photocatalytic pre-degradation agent to the fabric surface, and a reduction in UV pre-activation efficiency of about 40%; too long a processing time resulted in severe etching of the fabric surface, significant fiber mechanical damage, tensile strength decreased to 65% of that in Example 1, and obvious yellowing of the surface, resulting in unacceptable appearance.
[0098] The test results of Comparative Examples 12-15 showed that the tensile strength decreased by 29%-37% or the degradation efficiency was insufficient. Too low a light intensity during UV pre-activation resulted in insufficient activation of the photosensitive pre-degradation agent, with the active site density on the PET molecular chain being only 22% of that in Example 1, leading to a significant decrease in degradation efficiency. Too high a light intensity caused excessive oxidation and localized thermal damage to the PET molecular chain, resulting in microcracks on the wire surface and a decrease in tensile strength to 71% of that in Example 1. Furthermore, the lattice structure of the luminescent material was partially destroyed due to localized overheating, causing a permanent attenuation of approximately 25% in afterglow brightness. Too short a time duration failed to fully activate the photosensitive pre-degradation agent, with the active site density being only 35% of that in Example 1. Too long a time duration led to excessive photo-oxidation of the polymer molecular chain, resulting in a decrease in tensile strength to 63% of that in Example 1, and the processing energy consumption was too high, making industrial production costs unacceptable.
[0099] The comparative data above fully demonstrates that the combination of parameter ranges specified in this application is not arbitrarily chosen, but rather a synergistically optimal window determined through systematic experimental verification. Exceeding the specified range for any single parameter will lead to unacceptable degradation in at least one of the three core performance indicators: luminescence, mechanical properties, and degradation, thus failing to simultaneously meet the comprehensive requirements of sports shoes for safety warnings, mechanical performance, and environmental degradation.
[0100] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0101] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0102] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.
Claims
1. A biodegradable fabric that glows in the dark, characterized in that, The invention includes a biodegradable luminescent wire, which comprises a substrate, a luminescent material, a photosensitive pre-degradation agent, and a biodegradation promoter. The polymer molecular chains in the substrate undergo photo-oxidation under the combined action of the photosensitive pre-degradation agent and ultraviolet light to form polar functional groups and break the molecular chains.
2. The biodegradable fabric according to claim 1, characterized in that, In the aforementioned luminescent biodegradable wire: the substrate accounts for 85%-92% by mass, the luminescent material accounts for 5%-10% by mass, the photosensitive pre-degradation aid accounts for 1%-3% by mass, and the biodegradation promoter accounts for 2%-5% by mass.
3. The biodegradable fabric according to claim 1, characterized in that, The luminescent material includes at least one of strontium aluminate rare earth luminescent material, silicate system luminescent material, and sulfur oxide luminescent material; The photosensitive pre-degradation aid includes at least one of photosensitive rare earth cerium complexes, organotransition metal salts, and benzophenone photoinitiators.
4. The biodegradable fabric according to claim 1, characterized in that, The luminescent biodegradable thread comprises a core-sheath composite spun yarn, wherein the sheath of the core-sheath composite spun yarn includes the substrate, and the luminescent material, photosensitive pre-degradation aid, and biodegradation promoter are disposed in the core layer of the core-sheath composite spun yarn.
5. The biodegradable fabric according to claim 4, characterized in that, In the core layer of the core-sheath composite spinning, the total mass percentage of the luminescent material, photosensitive pre-degradation aid, and biodegradation promoter is 11.5%-25.5%.
6. The biodegradable fabric according to claim 4, characterized in that, The mass ratio of the sheath to the core layer in the sheath-core composite spinning is (20-40):(60-80). In the fabric, the total mass percentage of the luminescent material, photosensitive pre-degradable agent and biodegradable accelerator is 8%-18%.
7. The biodegradable fabric according to claim 1, characterized in that, The fabric comprises a three-dimensional mesh structure formed by warp knitting of the biodegradable luminescent yarn.
8. A method for manufacturing a biodegradable luminescent fabric, characterized in that, include: Prepare a phosphorescent biodegradable wire comprising a substrate, a phosphorescent material, a photosensitive pre-degradation agent, and a biodegradation promoter; Breathable fabrics with a three-dimensional mesh structure are prepared using the aforementioned biodegradable luminescent yarn through warp knitting. The breathable fabric is subjected to plasma surface activation treatment and then shaped to obtain a biodegradable fabric with luminescence. The biodegradable fabric is pre-activated with ultraviolet light.
9. The method for manufacturing the biodegradable luminescent fabric according to claim 8, characterized in that, The plasma surface activation treatment includes: In a vacuum environment of 20Pa-50Pa, oxygen is introduced and plasma is excited to oxidize and modify the surface of the breathable fabric for 30s-90s.
10. The method for manufacturing the biodegradable luminescent fabric according to claim 8, characterized in that, The wavelength of the ultraviolet light is 254nm-365nm, and the intensity of the ultraviolet light is 50W / cm². 2 -100W / cm 2 The pre-activation duration is 5-15 minutes.